CGIAR launches the Asian Mega-Deltas Initiative in Bangladesh - Bernardo, Eisen (CGIAR System Organization, 2022)
CGIAR, together with government agencies and other relevant stakeholders, conducted the country launch of the Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD) in Dhaka, Bangladesh on 10 August 2022. With the goal of promoting resilient, inclusive, and productive Asian Mega-Deltas, the AMD initiative will focus on the three main deltas in Asia, such as Ganges-Brahmaputra Delta in Bangladesh and India, Irrawaddy Delta in Myanmar, and Mekong River Delta in Vietnam and Cambodia.